Combining aggregation-induced emission and instinct high-performance of polyarylene ether nitriles via end-capping with tetraphenylethene. (5th January 2022) - Wang, Pan; Liu, Xidi; Liu, Hai; He, Xiaohong; Zhang, Dawei; Chen, Jiaqi; Li, Ying; Feng, Wei; Jia, Kun; Lin, Jing; Li, Kui; Yang, Xulin
Graphical abstract: Highlights: Polyarylene ether nitriles (PEN) end-capped by AIEgen were obtained by one-pot synthesis strategy via stepwise polymerization. Average molecular weight has effects on thermal resistance, processability and AIE performance. PEN processed into flexible casting films and electrospun membranes with efficient blue emitting. Electrospun membranes exhibited much efficient AIE effect than that of casting films, which is probably associated to the oriented and aligned chains. Abstract: Polyarylene ether-based polymer, a thermoplastic with photoluminescence, can be further functionalized as a thermal resistant, tough and flexible optical material. We synthesized three different average molecular weights of cyan fluorescent polyarylene ether nitriles (PEN) end-capped with tetraphenylethene (TPE). All obtained polymers (P(1-3)-TPE) exhibited typical aggregation-induced emission (AIE) features under aggregation states in solvent-nonsolvent mixtures with a high absolute quantum yield of fluorescence ( ФF ) (0.301–0.395). Moreover, end-capping synthesis strategy preserved the intrinsic and satisfactory processability of PEN while introducing the conjugated TPE. The obtained polymers were processed into flexible casting films with ФF range from 0.154 to 0.182. P3-TPE with largest molecular weights exhibited the strongest AIE effect, excellent thermal resistance with a 5% weight loss at a temperature of 511 °C, and tensile strength of 80.9 MPa. In addition, end-capped PENs were fabricated as electrospun membranes, which exhibited more efficient emission ( ФF at 0.465–0.490) may mainly due to oriented and aligned chains than that of the casting films. The findings provide an operable approach for combining conjugated fluorophore and intrinsic performance of PEN. These features make the end-capped AIE-active PEN has potential applications in various optical fields, including flexible display, fluorescent sensing, and anti-counterfeiting.